American economic development : growth of the U. S. in the Western World - Levy, Lester Samuel; Sampson, Roy J. (Boston : Allyn and Bacon, 1962)
The central theme of this book is the development of socio-economic institutions in the Western World. It will be beneficial for freshman and sophomore students.
Includes bibliography.
rpm 16/06/2017
Loans
Keywords: Economic history; Economics; United States